Usages littéraires du merveilleux et effets d’attestation dans les littératures subsahariennes (Kwahulé, Mukasonga, Tchak) - Coste, Marion (HAL CCSD, 2022)
International audience This article focuses on Les Fables du moineau by Sami Tchak, Monsieur Ki by Koffi Kwahulé and Cœur Tambour by Scholastique Mukasonga. It is a question of analyzing the types of authority summoned in these stories. A first authority, moral, is based on a documentary value, the story translating sociological realities or belief systems attributed to sub-Saharan cultures, particularly through the use of the marvelous genre or the recall of the codes of the traditional tale, in the work of Sami Tchak. However, this authority, which would tend to undermine the artistic significance of the work, is counterbalanced by another type of authority, properly literary. The latter is expressed first of all by the emphasis on numerous stylistic effects, particularly in moments that call for the marvelous, which show the singularity of the writing of each author. It is also expressed through the effects of irony and by creating a distance, through the insertion of Western narrators (Mukasonga) or the figure of a doubtful reader (Kwahulé), which introduces into the stories a plurality of points of view and a critical distance on certain magico-religious explanations which are presented, at another level, as the expression of sub-Saharan cultures.